Echocardiographic markers of inducible myocardial ischemia at baseline evaluation preparatory to exercise stress echocardiography. Issue 1 (December 2015) - Cherubini, Antonella; Cioffi, Giovanni; Mazzone, Carmine; Faganello, Giorgio; Barbati, Giulia; Tarantini, Luigi; Russo, Giulia; Stefenelli, Carlo; Humar, Franco; Grande, Eliana; Fisicaro, Maurizio; Pandullo, Claudio; et al.
Abstract Background Tissue Doppler Imaging (TDI) is a sensible and feasible method to detect longitudinal left ventricular (LV) systolic dysfunction (LVSD) in patients with diabetes mellitus, hypertension or ischemic heart disease. In this study, we hypothesized that longitudinal LVSD assessed by TDI predicted inducible myocardial ischemia independently of other echocardiographic variables (assessed as coexisting potential markers) in patients at increased cardiovascular (CV) risk. Methods Two hundred one patients at high CV risk defined according to the ESC Guidelines 2012 underwent exercise stress echocardiography (ExSEcho) for primary prevention. Echocardiographic parameters were measured at rest and peak exercise. Results ExSEcho classified 168 (83.6 %) patients as non-ischemic and 33 (16, 4 %) as ischemic. Baseline clinical characteristics were similar between the groups, but ischemic had higher blood pressure, received more frequently beta-blockers and antiplatelet agents than non-ischemic patients. The former had greater LV size, lower relative wall thickness and higher left atrial systolic force (LASF) than the latter. LV systolic longitudinal function (measure as peak S') was significantly lower in ischemic than non-ischemic patients (8.7 ± 2.1 vs 9.7 ± 2.7 cm/sec, p  = 0.001). The factors independently related to myocardial ischemia at multivariate logistic analysis were: lower peak S', higher LV circumferential end-systolic stress and LASF. Conclusions In asymptomatic patients at increased risk for adverse CV events baseline longitudinal LVSD together with higher LV circumferential end-systolic stress and LASF were the factors associated with myocardial ischemia induced by ExSEcho. The assessment of these factors at standard echocardiography might help the physicians for improving the risk stratification among these patients for ExSEcho.